Not in your usual Top 10: protists that infect plants and algae. (11th October 2017) - Schwelm, Arne; Badstöber, Julia; Bulman, Simon; Desoignies, Nicolas; Etemadi, Mohammad; Falloon, Richard E.; Gachon, Claire M. M.; Legreve, Anne; Lukeš, Julius; Merz, Ueli; Nenarokova, Anna; Strittmatter, Martina; et al.
Summary: Fungi, nematodes and oomycetes belong to the most prominent eukaryotic plant pathogenic organisms. Unicellular organisms from other eukaryotic lineages, commonly addressed as protists, also infect plants. This review provides an introduction to plant pathogenic protists, including algae infecting oomycetes, and their current state of research.